2019
DOI: 10.1177/1473325019893412
|View full text |Cite
|
Sign up to set email alerts
|

Child removal as the gateway to further adversity: Birth mother accounts of the immediate and enduring collateral consequences of child removal

Abstract: This article is focused on the immediate and enduring consequences of child removal, from the perspective of birth mothers. The article builds on the authors’ previous theoretical work on the collateral consequences of child removal and women’s vulnerability to repeat family court appearances. Interview data drawn from in-depth qualitative interviews with 72 birth mothers conducted in seven local authority areas are revisited to enable a focused analysis of the immediate and longer-term effects of child remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 43 publications
5
113
0
Order By: Relevance
“…They give the example of one woman in the study who was forced to move from a two-bedroom home into a hostel, where she was living among drug users and subsequently became addicted herself. This research also shows how stigma 'plays out in multiple settings for this group of women-who feel discredited in both interpersonal and professional encounters' [10] (p. 15), noting that a sense of being pre-judged could contribute to women's isolation and make it more difficult for them to access support. Schofield and colleagues' research with parents of children in foster care similarly documented their fear (and experiences) of 'being seen as, or even having become, a 'different' as well as unworthy person' [12] (p. 83).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…They give the example of one woman in the study who was forced to move from a two-bedroom home into a hostel, where she was living among drug users and subsequently became addicted herself. This research also shows how stigma 'plays out in multiple settings for this group of women-who feel discredited in both interpersonal and professional encounters' [10] (p. 15), noting that a sense of being pre-judged could contribute to women's isolation and make it more difficult for them to access support. Schofield and colleagues' research with parents of children in foster care similarly documented their fear (and experiences) of 'being seen as, or even having become, a 'different' as well as unworthy person' [12] (p. 83).…”
Section: Introductionmentioning
confidence: 78%
“…Approximately 40% had been in care themselves as children (and late care entry and multiple placement moves were reported by half), and at least two-thirds had experienced abuse and/or neglect in childhood. This research also revealed how the collateral consequences of child removal increase risks for recurrence [9][10][11], highlighting the need for policy and services to respond to the support needs of mothers as well as the risks for their children.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Increases in infant removals have been noted in countries with risk-focused child protection systems (Alrouh et al 2019;Bilson and Bywaters, 2020;Broadhurst et al 2018;Marsh et al 2017;O'Donnell et al 2016). The work of Broadhurst, Mason and colleagues in England and Wales has further demonstrated the lasting difficulties that this causes for birth mothers, and the risk of 'recurrent' care proceedings (Broadhurst et al 2017;Broadhurst and Mason, 2020;Griffiths et al, 2020). Inequalities in rates of removal from different geographical areas of England have been noted (Bilson and Bywaters, 2020;Broadhurst et al 2018).…”
Section: Infants Health and Riskmentioning
confidence: 99%